2018
DOI: 10.3390/nano8040222
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Correlated, Single Nanomaterial-Level Structural and Optical Profiling of Cu-Doped ZnO Nanorods Synthesized via Multifunctional Silicides

Abstract: We demonstrate a straightforward and effective method to synthesize vertically oriented, Cu-doped ZnO nanorods (NRs) using a novel multipurpose platform of copper silicide nanoblocks (Cu3Si NBs) preformed laterally in well-defined directions on Si. The use of the surface-organized Cu3Si NBs for ZnO NR growth successfully results in densely assembled Cu-doped ZnO NRs on each NB platform, whose overall structures resemble thick bristles on a brush head. We show that Cu3Si NBs can uniquely serve as a catalyst for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…As it is critical to tune the NRs’ properties in such applications, various approaches have been employed to control the nanomaterials’ optical, electrical, and piezotronic behaviors. They include changing chemical compositions through doping [ 16 , 17 , 18 ], altering crystalline structures [ 19 , 20 , 21 , 22 ], and applying a magnetic field [ 23 ]. More recently, mechanical strain has also been used to modulate ZnO properties [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…As it is critical to tune the NRs’ properties in such applications, various approaches have been employed to control the nanomaterials’ optical, electrical, and piezotronic behaviors. They include changing chemical compositions through doping [ 16 , 17 , 18 ], altering crystalline structures [ 19 , 20 , 21 , 22 ], and applying a magnetic field [ 23 ]. More recently, mechanical strain has also been used to modulate ZnO properties [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another field of applied science currently benefitting from hybrid materials is health care. Potential biomedical applications are envisaged in the works by Truong et al [ 18 ] and by Predoi et al [ 19 ]. Truong and coauthors [ 18 ] reported the synthesis of vertically aligned Cu-doped Zn nanorods grown on a platform of Cu 3 Si nanoblocks.…”
mentioning
confidence: 99%
“…Potential biomedical applications are envisaged in the works by Truong et al [ 18 ] and by Predoi et al [ 19 ]. Truong and coauthors [ 18 ] reported the synthesis of vertically aligned Cu-doped Zn nanorods grown on a platform of Cu 3 Si nanoblocks. The prepared nanocomposites showed an extended absorption edge and bioluminescence in the visible region, which paves the way to their application as bio-probes and luminescent markers.…”
mentioning
confidence: 99%